2007
DOI: 10.1074/jbc.m608140200
|View full text |Cite
|
Sign up to set email alerts
|

Glutathionylation of Trypanosomal Thiol Redox Proteins

Abstract: Trypanosomatids, the causative agents of several tropical diseases, lack glutathione reductase and thioredoxin reductase but have a trypanothione reductase instead. The main low molecular weight thiols are trypanothione (N 1 ,N 8 -bis-(glutathionyl)spermidine) and glutathionyl-spermidine, but the parasites also contain free glutathione. To elucidate whether trypanosomes employ S-thiolation for regulatory or protection purposes, six recombinant parasite thiol redox proteins were studied by ESI-MS and MALDI-TOF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 55 publications
2
29
0
Order By: Relevance
“…45 47 or Cys 95 but not of both residues in the same protein molecule (48). Modification of one cysteine probably interferes sterically with the modification of the second one in accordance with the structural data that also in the reduced form of Px III both cysteines lie in close proximity.…”
Section: Discussionsupporting
confidence: 82%
“…45 47 or Cys 95 but not of both residues in the same protein molecule (48). Modification of one cysteine probably interferes sterically with the modification of the second one in accordance with the structural data that also in the reduced form of Px III both cysteines lie in close proximity.…”
Section: Discussionsupporting
confidence: 82%
“…Protein (de)glutathionylation is a reversible regulatory mechanism in which Grxs play a pivotal role (5,6). Previously, we demonstrated that several thiol redox proteins of T. brucei are susceptible to specific glutathionylation in vitro (59). As shown here, both parasite Grxs catalyze the reduction of GSH mixed disulfides of BSA, TXNPx, or 2-mercaptoethanol.…”
Section: Table 2 Reduction Of Glutathionylated Model Substrates By DIsupporting
confidence: 68%
“…2A). In contrast to the specificity displayed by E. coli Grx4 and S. cerevisiae Grx5, Cys181-not Cys104-forms a mixed disulfide with GSH and Gsp (58), which can trigger the formation of an intramolecular Cys104-Cys181 disulfide bridge (16,58). In vitro, both oxidation states are reduced by TXN or the T(SH) 2 /TR system (27,58).…”
Section: Oligomeric State and Redox Properties Of The T Brucei 1-c-grxsmentioning
confidence: 96%
“…An N-terminal region of about *37 residues, exclusive of the kinetoplastid 1-C-Grx1s, has recently been identified to be responsible for dimerization of the T. brucei and T. cruzi proteins (55a). In vitro, T. brucei 1-CGrx1 lacks any general thiol-disulfide oxidoreductase activity (27) but is susceptible to oxidation by GSSG and Gsp disulfide (16,58). In addition to the active site Cys104, T. brucei 1-CGrx1 contains a second cysteine, namely Cys181, located at the fourth position from the C-terminus ( Fig.…”
Section: Oligomeric State and Redox Properties Of The T Brucei 1-c-grxsmentioning
confidence: 99%
See 1 more Smart Citation